PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 006 MUDA SETIA SEKIJANG KAB. PELALAWAN - Eka Aprila; Erlisnawati Erlisnawati; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The problem this research is the students achievement of social fourth graderes studies still low with an average value of 63,2 and minimum completeness criteria (KKM) social studies is 70. Between students, amounting to 25 people only 10 students who achieve classical KKM with 40%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of social studies class IV at SDN 006 Muda Setia Sekijang with implementation cooperative learning model type Make a Match. Formulation of the problem : Is the implementation of cooperative learning model type Make a Match can improve students achievement of social studies at SDN 006 Muda Setia Sekijang. The research was conducted on November 14, 2013 to November 28, 2013 by 2 cycles. Subjects were students of SDN 006 Muda Setia Sekijang, totaling 25 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 63,2. In the first cycle improve an average of 71,2 with increase big as 12,65% and an improve in the second with an average of 80,4 with increase big as 27,21%. Activities of the teacher in the learning process in the cycle I with the first meeting of an average of 62,5% and a second meeting improve to 70,83%. Cycle II first meeting of an average of 91,66% and a second meeting improve to 95,33%. Results of data analysis of students activities in the cycle I with the first meeting of an average of 58,33% and a second meeting improve to 62,5%. Cycle II first meeting of an average of 79,16% and a second meeting improve to 91,66%. Results in the class IV at SDN 006 Muda Setia Sekijang that the implementation of cooperative learning model of Make a Match can improve the student achievement of social studiesat fourth graderes SDN 006 Muda Setia Sekijang.Key Words: Make a Match, fourth graderes Students Achievement.